Foreign Labor Entry: Effect on Unemployment, Economic Growth and Security Implication in Malaysia - Malarvili, Loganathan (2011)
A foreign worker is a person who works in a country other than the one of which he or she is a citizen. Therefore, attendance foreign workers in Malaysia are to help the country overcome the shortage of workers. In fact, it helps to achieve economic growth. Significantly, entry of foreign workers was since the late 1980s. Initially, most of them work as laborers in the formal sector, but then many are turning to business. It directly effect on unemployment rate, economy growth and security implication in Malaysia. The general objective of this study is to analyze the foreign labor entry: effect on unemployment, economy growth and security implication in Malaysia. This study will use a time series data to test weather rises in foreign labor effect on unemployment rate and economic growth in Malaysia by Cointegration Test, Granger Casuality Test and Ordinary Least Square Test. Data was collected from Department of Statistic Malaysia, royal Malaysia Police, Economic Planing Unit and World Bank. The results show that, there are both positive and negative impacts on economy growth. Therefore national policies on employment of foreign worker are suited to the need of country. Government spends more expenses to establish new security implication to overcome this which one of losses to the country. In conclusion, despite the presence of these foreign labors can help countries overcome labor shortages and help achieve the economic growth rate is fixed cause problems.